Dielectric relaxation in NaNbO₃ single crystal - Konieczny, K. (Condensed Matter Physics, 1999)
Dielectric permittivity studies of reduced samples of NaNbO₃ single crystal in the range of temperatures 30–500 °C and frequency 20 Hz-1 MHz are reported. In this temperature range a relaxation process is observed in the frequency range of about 100 kHz. This is an additional process to the earlier reported one [7]. The obtained data were ﬁtted to Cole-Cole formula. The dispersion step ∆ǫ (the maximum value of ∆ǫ =1000) is temperature dependent. The mean relaxation time τ does not obey the Arrhenius law above TC. The occurrence of this relaxation process may be connected with oxygen vacancies. Досліджено діелектричну сприйнятливість зразків монокристалу NaNbO₃ в діапазонах температур 30–500 °C і частот 20 Гц–1 МГц. У цьому температурному проміжку в частотній області поблизу 100 кГц спостерігається релаксаційний процес, що є доповнювальним до виявленого раніше процесу [7]. Отримані дані апроксимуються за формулою Коул-Коула. Значення дисперсії ∆ε (максимальне значення ∆ε = 1000) залежить від температури. Закон Арреніуса не виконується для середнього часу релаксації τ вище TC. Поява цього релаксаційного процесу може пов’язуватися з кисневими вакансіями.